2009
DOI: 10.1073/pnas.0903875106
|View full text |Cite
|
Sign up to set email alerts
|

Functional muscle regeneration with combined delivery of angiogenesis and myogenesis factors

Abstract: Regenerative efforts typically focus on the delivery of single factors, but it is likely that multiple factors regulating distinct aspects of the regenerative process (e.g., vascularization and stem cell activation) can be used in parallel to affect regeneration of functional tissues. This possibility was addressed in the context of ischemic muscle injury, which typically leads to necrosis and loss of tissue and function. The role of sustained delivery, via injectable gel, of a combination of VEGF to promote a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
369
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 385 publications
(382 citation statements)
references
References 62 publications
(80 reference statements)
12
369
0
1
Order By: Relevance
“…Another study showed that intramuscular administration of a plasmid engineered to induce VEGF expression enhanced preserved grip strength in a rat model of amyotrophic lateral sclerosis which suggests that VEGF administration might be neuroprotective and a practical approach for treating motor disorders [16]. Although data on muscle force restoration after musculoskeletal injury for this type of model were not available at the time we conducted our study, recently published studies [2,4] confirm the restoration of muscle force we observed.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Another study showed that intramuscular administration of a plasmid engineered to induce VEGF expression enhanced preserved grip strength in a rat model of amyotrophic lateral sclerosis which suggests that VEGF administration might be neuroprotective and a practical approach for treating motor disorders [16]. Although data on muscle force restoration after musculoskeletal injury for this type of model were not available at the time we conducted our study, recently published studies [2,4] confirm the restoration of muscle force we observed.…”
Section: Discussionsupporting
confidence: 68%
“…We also suspect VEGF might have had more a direct effect on stimulating myogenesis, as we saw better muscle regeneration rather than contributing to repair by aiding neovascularization as the number of vessels did not increase. In addition, this might be explained by the mechanism that VEGF stimulates satellite cell activation and proliferation, cells are protected from apoptosis, the inflammatory response is muted, and highly functional muscle tissue is formed [4]. Furthermore, muscle regeneration appears to be mediated by MDSCs [7] which are superior to myoblasts in terms of proliferating ability, multipotent differentiation, and strong self-renewal [27].…”
Section: Discussionmentioning
confidence: 99%
“…The field continues to expand and tissue bioengineering has provided, or is close to delivering, functional human organ replacements elsewhere (6,7,(13)(14)(15)(16)(17). The ability to produce innervated and revascularized muscles would hugely extend the possible applications of regenerative medicine (18)(19)(20)(21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%
“…In other studies, IGF and VEGF delivery was shown to prevent cellular damage by apoptosis or necrosis. 97,99 In addition to cell survival, small molecule/growth factor delivery can also be utilized to promote vascularization processes and improve functionality of tissue constructs. 51,55,100,101 For example, in one study angiopoietin-1 and VEGF were incorporated into hyaluronan gels with and without heparin.…”
Section: Growth Factor Delivery For Cardiac Tissue Engineeringmentioning
confidence: 99%